2022
DOI: 10.34172/joddd.2022.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the posterior stop on temporomandibular disorders: A systematic review

Abstract: Background. Temporomandibular disorders have common signs and symptoms, including pain in the masticatory muscles, limitation or deviation in a mandibular range of motion, and other common patient complaints, such as headache and earache. The main focus of this study was to collect comprehensive and integrated data on the effect of the posterior stop on temporomandibular joint disorders, as well as prevention, treatment, and follow-up care for the patients. Methods. The authors conducted the search in PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…While some lesions are benign, others are premalignant or manifestations of systemic diseases. Therefore, timely diagnosis is essential, especially given that the treatment approaches differ for different diseases [ 3 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some lesions are benign, others are premalignant or manifestations of systemic diseases. Therefore, timely diagnosis is essential, especially given that the treatment approaches differ for different diseases [ 3 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Khanghani et al suggested insufficient awareness of dentists and dental students about the transmission of infectious diseases 28 . Studies have shown that less developed countries use fewer personal protection measures; thus, only 25% of dentists in Iran wear protective gloves, compared to 90% in Western Europe and North America 28 .…”
Section: Continuous Educationmentioning
confidence: 96%
“…In their study, Khanghani et al suggested insufficient awareness of dentists and dental students about the transmission of infectious diseases 28 . Studies have shown that less developed countries use fewer personal protection measures; thus, only 25% of dentists in Iran wear protective gloves, compared to 90% in Western Europe and North America 28 . Guruprasad et al indicated that professional staff and the media 18,24 provide little support for the education of dental staff about the risks of infection transmission and protective measures.…”
Section: Continuous Educationmentioning
confidence: 96%
See 2 more Smart Citations